HUBUNGAN DISIPLIN KERJA PERAWAT DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT AWET MUDA NARMADA KABUPATEN LOMBOK BARAT - Alwan Wijaya; Qoni Nurlaili; Ageng Abdi Putra (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2026)
Introduction: Health services provided by hospitals constitute an essential form of public service in meeting the basic healthcare needs of the community. Nurses, as frontline healthcare professionals, play a crucial role in determining the quality of hospital services. Optimal nurse performance is influenced by various factors, one of which is work discipline. Nurses' work discipline encompasses compliance with regulations, punctuality, adherence to standard operating procedures (SOPs) in performing duties, accountability, and professionalism in delivering nursing care. Poor work discipline may result in delays in service delivery, incomplete documentation, and a decline in the quality of patient care. Objective: to determine the relationship between nurses' work discipline and their performance in the inpatient unit of Awet Muda Regional General Hospital, Narmada, West Lombok Regency. Methods: This quantitative study employed a correlational research design with a cross-sectional approach. The study population comprised all nurses working in the inpatient units (IRNA A, IRNA B, IRNA C, and IRNA D) of Awet Muda Regional General Hospital, Narmada, totaling 40 nurses. A purposive sampling technique was employed, and all 40 nurses were included as the study sample. Data were collected using a work discipline questionnaire and a nurse performance questionnaire. Data were analyzed using Spearman's rank correlation test. Results: The results show that the majority of respondents have good work discipline, particularly in terms of compliance with the hospital's SOPs (92.50%), responsibility (85%), and punctuality (85%). Nurse performance is also categorized as good, especially with respect to the accuracy of documentation (97.50%), maintaining patient confidentiality (95%), and timely documentation following nursing interventions (90%). Spearman's rank correlation test reveals a correlation coefficient (r) of 0.756 with a significance value of p = 0.000 (p < 0.05), indicating a strong, positive, and statistically significant relationship between nurses' work discipline and their performance. Conclusion: There is a strong and statistically significant relationship between nurses' work discipline and their performance, with a correlation coefficient of r = 0.756 and a significance value of p = 0.000 (p < 0.05). The relationship is positive, indicating that better work discipline is associated with better nurse performance. Future researchers are recommended to investigate other variables, such as motivation, workload, and leadership.